2010
DOI: 10.1152/physiolgenomics.00145.2009
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves muscle vasodilatation in individuals with T786C polymorphism of endothelial nitric oxide synthase gene

Abstract: Rondon MU. Exercise training improves muscle vasodilatation in individuals with T786C polymorphism of endothelial nitric oxide synthase gene. Physiol Genomics 42A: 71-77, 2010. First published July 6, 2010; doi:10.1152/physiolgenomics.00145.2009.-Allele T at promoter region of the eNOS gene has been associated with an increase in coronary disease mortality, suggesting that this allele increases susceptibility for endothelial dysfunction. In contrast, exercise training improves endothelial function. Thus, we hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
7
0
4
Order By: Relevance
“…Overall, these studies have shown that the presence of a polymorphism for the NOS3 gene attenuates the beneficial effect of exercise training measured by flow-mediated dilatation (19,43), BP (46,53,54), and NO production (54). In contrast, some studies have shown that exercise training overcomes the unfavorable effect of NOS3 gene polymorphisms on cardiometabolic responses (64,65), whereas others have shown that volunteers with NOS3 gene polymorphisms are equally responsive in lowering BP to exercise training compared with subjects without NOS3 gene polymorphisms (20,49).…”
mentioning
confidence: 95%
“…Overall, these studies have shown that the presence of a polymorphism for the NOS3 gene attenuates the beneficial effect of exercise training measured by flow-mediated dilatation (19,43), BP (46,53,54), and NO production (54). In contrast, some studies have shown that exercise training overcomes the unfavorable effect of NOS3 gene polymorphisms on cardiometabolic responses (64,65), whereas others have shown that volunteers with NOS3 gene polymorphisms are equally responsive in lowering BP to exercise training compared with subjects without NOS3 gene polymorphisms (20,49).…”
mentioning
confidence: 95%
“…Carriers of CC genotype showed greater increase in forearm vascular conductance during exercise than carriers of allele T. In a study with 72 healthy and physically active individuals, carriers of eNOS 786TT genotype showed impaired exercise forearm vasodilatation than carriers of eNOS 786TC and 786CC genotypes, which allowed the hypothesis that T allele may increase susceptibility for endothelial dysfunction [12]. Interestingly, in this study, carriers of eNOS 786TT genotype, despite worse baseline exercise vasodilatation, had better improvement in muscle vasodilatation after 18 week-exercise training than carriers of eNOS 786C allele.…”
Section: Discussionmentioning
confidence: 97%
“…Studies with small samples, ranging from 33 to 72 participants, have suggested that muscle vasodilatation during exercise may be modulated by functional polymorphisms in genes of physiologic pathways linked to cardiovascular regulation such as beta-adrenergic receptors, bradykinin B 2 receptor (BDKRB 2) and endothelial nitric oxide synthase (eNOS) [10], [11], [12], [13]. Additionally, experimental studies with healthy individuals have demonstrated that alpha-adrenergic receptors mediate an important role on the modulation of the vascular tonus at rest [14] and during exercise [15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients carrying C allele at T −786 → C had a smaller improvement in APV (~36%) than patients carrying T allele (~ 81%), whereas a polymorphic effect of G 894 → T was not observed. Similarly, 18 weeks of exercise training increased forearm vascular conductance during handgrip exercise in TT carriers, but not in CT or CC carriers at T −786 → C of NOS3 (Negrao et al, 2010). For other vascular-related genes, there is limited information regarding their role in improved endothelial function with exercise training (Park et al, 2007; Alves et al, 2013; Lemos et al, 2016).…”
Section: Genetic Regulation Of Endothelial Function In Humansmentioning
confidence: 97%